2013
DOI: 10.2215/cjn.13091211
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Nutritional Supplementation and Clinical Outcomes among Patients with ESRD

Abstract: SummaryBackground and objectives Oral nutritional supplementation (ONS) was provided to ESRD patients with hypoalbuminemia as part of Fresenius Medical Care Health Plan's (FMCHP) disease management. This study evaluated the association between FMCHP's ONS program and clinical outcomes. Results Among patients with indication for ONS, 276 received supplements and 194 did not. ONS use was associated with 0.058 g/dl higher serum albumin overall (P=0.02); this difference decreased by 0.001 g/dl each month (P=0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 15 publications
1
53
0
5
Order By: Relevance
“…Two recent large-scale observational studies reported significant survival benefit in hypoalbuminemic maintenance HD patients receiving nutritional supplementation compared with matched controls (53,54). In a retrospective cohort study of 4289 matched pairs, death rates were 30.9% versus 37.3% in the treated versus untreated groups, respectively (53).…”
Section: Treatment Of Pew: An Integrated Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent large-scale observational studies reported significant survival benefit in hypoalbuminemic maintenance HD patients receiving nutritional supplementation compared with matched controls (53,54). In a retrospective cohort study of 4289 matched pairs, death rates were 30.9% versus 37.3% in the treated versus untreated groups, respectively (53).…”
Section: Treatment Of Pew: An Integrated Approachmentioning
confidence: 99%
“…Reprinted from reference 52, with permission. disease management plan in maintenance HD patients, ONS use was associated with higher serum albumin and lower hospitalization rate at 1 year, without reduction in mortality risk, compared with patients who did not receive ONS (54). The limitations of these studies include their retrospective design, convenience sampling, and residual confounding from unmeasured variables.…”
Section: Treatment Of Pew: An Integrated Approachmentioning
confidence: 99%
“…Finally it is important to remember that the relevance of the regular nutritional assessment in patients with CKD is not solely in recognizing the presence of a problem but also, or even primarily, in providing adequate nutritional support intended to alleviate the problem. There is ample evidence published in the literature that nutritional support of malnourished patients with CKD leads to an improvement of nutritional status parameters, lowering of markers of chronic inflammation, a better quality of life and decreased number of hospitalizations (16)(17)(18)(19)(20)(21). Our patients will be grateful for these outcomes, particularly the latter two.…”
Section: Introductionmentioning
confidence: 85%
“…En los pacientes con ERC, el estado nutricional es uno de los principales predictores de morbimortalidad, por lo cual su evaluación y manejo deben hacer parte de un tratamiento integral 6,7 . La frecuencia de malnutrición en pacientes con ERC es de hasta 40 %, según estudios hechos en España, y se ha visto relacionada con una disminución en la sobrevida, incremento de la estancia hospitalaria y mayores costos 8 …”
Section: Introductionunclassified